Genopolitics: A New Approach in Political Behavior - Ali Sahab; Aribowo Aribowo (Masyarakat, Kebudayaan dan Politik, 2023)
This study is about the influence of genes on political attitudes and behavior in the subfield of biopolitics. Genopolitics arose as a critique of the political science approach which was deemed insufficient to explain political attitudes and behavior both theoretically and methodologically. To find the origins of political attitudes and behavior, interdisciplinary studies are needed. It is genes that can explain the origin of individual preferences on which all rational choices are based. The method used in this study was a literature review to see the development of genopolitics, debates, and criticisms related to political attitudes and behavior from the point of view of political science and genopolitics. The literature used was derived from books, journals, magazines, and news on the internet. Regarding voter turnout, 32 different social factors can only be explained by 31% by differences in political behavior, while the remaining 69% of differences can be explained by genetic differences. This study concludes that genopolitics as a new approach used to see political attitudes and behavior can be applied in Indonesia to answer and complete the survey-based study of political behavior.